Geotechnical properties of lateritic soil as subgrade and base material for road construction in Abeokuta, Southwest Nigeria - Oluyinka, Layade Gideon; Olubunmi, Ogunkoya Charles (International Journal of Advanced Geosciences, 2018)
Lateritic soils that overburden Mohammad Buhari Estate in Abeokuta area of Ogun State, Nigeria is in great use for road construction. However, little is known of their geotechnical properties and suitability as base, sub-based and sub-grade materials for road construction. This study is aimed at utilizing in accordance with regulatory standards of Nigeria, the geotechnical techniques to investigate the properties of this lateritic soil. The samples were collected at 0. 25m deep at different locations and were subjected to the following laboratory test; Particle size analysis, Atterberg limits test, Compaction test, Californian Bearing Ratio test, Moisture content and Specific gravity test. The result shows un-soaked CBR test from 12.52-55.84 %. The specific gravity results range from 2.57-2.89 while the optimum moisture content and maximum dry density range from 18.20-28.30% and 1.48-1.81mg/m3 respectively. The liquid limit, plastic limit and plastic index ranges from 12.0 to 40.1%, 10.0 to 22.0% and 2.8 to 20.4% respectively. This implies that lateritic soil present throughout the study area is suitable for use as sub-base and base materials since the geotechnical properties are fairly within the regulatory standards of Nigeria.